If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + -3b = 10 Solving 4a + -3b = 10 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '3b' to each side of the equation. 4a + -3b + 3b = 10 + 3b Combine like terms: -3b + 3b = 0 4a + 0 = 10 + 3b 4a = 10 + 3b Divide each side by '4'. a = 2.5 + 0.75b Simplifying a = 2.5 + 0.75b
| 10x-x-134=118 | | 1.5x+3x-4=10 | | 15p+7p= | | 2x^2-5x-133=0 | | S=D+pm | | 3*3/10+4=-3 | | -2W+5-3W-4=-9 | | 3*-7/4+4=-3 | | 2.4(2x-2)+2.2x= | | .06x+.5=.123 | | X+45=600 | | (11b-6)-5(2b+4)=-6 | | 10(x+5)=12(x-4) | | 17p+14+19=3 | | x=2*tanh(x) | | 14m=400.0 | | 10x+12=32 | | x=tanh(x) | | x-4.2=6 | | 12.67(a-3)=.5 | | 1.4y=7 | | -6(4x-3)+5(5x-4)-8=7-8 | | 2(y-2)-4=10 | | 2x^2-5x+245=0 | | -3n+9=-4n+5 | | 3X+4-5X=-10 | | 12x^4+x^2-6=0 | | 60+2x=7(x+60) | | X^2+y^2+Z^2=50 | | -3n+9=-4+5 | | 60+2x=7(x+30) | | 3d+8=2(d+4) |